IMPLEMENTATION OF AFTERLIFE INVESTMENT IN EDUCATION AT NURUL WAHID AL-ISLAMI FOUNDATION - Mu'ammar Nurkhalis Akmal; Muhammad Ulama; Ahmad Ridwan (Jurnal Scientia, 2023)
To realize quality human resources requires direction from education and development policies that strongly focus on education as an investment in the future. As an investment in the future, compulsory education has been carried out from an early age as a continuous and systemic program taken in various policy programs, which starts from early childhood education, primary education, and secondary education, to higher education. To make the program successful, various improvements in education policy for all future generations of the nation have been determined, improving the quality of educators and education programs in Indonesia.